1986
DOI: 10.1128/mcb.6.7.2721
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin isoform switching in tumorigenic human fibroblasts.

Abstract: We identified six tropomyosin (Tm) isoforms in diploid human fibroblasts. We used computerized microdensitometry of 2-dimensional protein profiles to measure the relative rates of synthesis and abundance of the individual Tm isoforms and actin, the two major structural constituents of microfilaments. In carcinogen-transformed human fibroblasts (HuT-14), the rates of synthesis of three Tm isoforms (Tml, Tm2, and Tm6) were greatly decreased relative to normal diploid parental fibroblasts and to actin. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 28 publications
2
73
1
Order By: Relevance
“…These cells also exhibit abnormal expression of the tropomyosin isoforms (11). We have now found that, after introduction and expression of functional (-or -y-actin gene clones in HuT-14T cells, we can alter the ,IBy actin synthesis ratios to greater degrees than in the cell lines previously studied, which have all of their normal actin alleles.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…These cells also exhibit abnormal expression of the tropomyosin isoforms (11). We have now found that, after introduction and expression of functional (-or -y-actin gene clones in HuT-14T cells, we can alter the ,IBy actin synthesis ratios to greater degrees than in the cell lines previously studied, which have all of their normal actin alleles.…”
mentioning
confidence: 65%
“…This abundant expression of the transfected mutant 1B-actin gene also resulted in changes in cell morphology and concomitant reduction of rates of synthesis of five of six tropomyosin isoforms (12,13 transformation of avian, rodent, and human fibroblasts (1,2,5,11,15). Furthermore, abundant expression of mutant (-actin in immortalized, nontumorigenic human HuT-12 fibroblasts led to stable tumorigenic conversion of a subpopulation of transfected cells which exhibited enhanced mutant ,B-actin synthesis (13).…”
mentioning
confidence: 99%
“…For example, suppression of high M r TMs, viz., isoforms 1 and 2 (TM1 and TM2, respectively), is nearly universal in all the transformed cell lines tested, while elevated levels of the low M r species such as TM4 and TM5 are reported in some malignant cell types (Bhattacharya et al, 1990;Cooper et al, 1985Cooper et al, , 1987Hendricks and Weintraub, 1981;Leavitt et al, 1986;Matsumura et al, 1983). Although all TMs bind to actin with varying binding a nities, the precise function of each of the isoforms remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In non-muscle cells, the role of tropomyosins is less clearly understood, and it is generally thought that they are involved in stabilization of actin microfilaments which, in turn, play an important role in maintaining cell shape, motil-ity, and interaction with extracellular supporting elements (Pollard et al, 1976;CBtC, 1983;Stossel et al, 1985). The terminology of tropomyosins used in this study is one in general use for tropomyosins expressed in fibroblasts (Leavitt et al, 1986). Tropomyosins-1-3 correspond, in increasing order of electrophoretic mobility, to the high-Mr tropomyosins (284 amino acids), which are homologous to tropomyosins expressed in muscle cells, while tropomyosin-4 and tropomyosin-5 correspond to the low-M, tropomyosins (247 or 248 amino acids) characteristic of non-muscle cells.…”
mentioning
confidence: 99%
“…The reader is also referred to footnote 2 of Lehrer and Qian (1990) regarding the terminology of smooth muscle tropomyosins. A number of studies have shown that down-regulation of expression of the high-M, tropomyosin isoforms consistently accompanies neoplastic transformation of murine and avian fibroblasts by a variety of retroviral oncogenes, chemical mutagens and transforming growth factors (Hendricks and Weintraub, 1981;Leonardi et al, 1982;Matsumura et al, 1983;Hendricks and Weintraub, 1984;Cooper et al, 1985Cooper et al, , 1987Leavitt et al, 1986). These findings have led to the proposal that deficiency of tropomyosin expression may be a causal biochemical event in neoplastic transforma-tion by many modalities, acting to destabilize the actin microfilaments (Cooper et al, 1985).…”
mentioning
confidence: 99%